CONSTRUCTING ISLAMIC BANKING RESILIENCE INDEX IN INDONESIA - Wiranatakusuma, Dimas Bagus (Journal of Islamic Monetary Economics and Finance, 2018)
Islamic banking plays critical roles in providing many essential economic functions and services to the entire financial system and the overall economy. Thus, a strong and the resilience of Islamic banking is the foundation and pre-condition for achieving sustainable economic growth, given that banks are at the centre of the credit intermediation process between savers and investors. One of the main causes of past financial crisis was that the banking sector had built up excessive both on-and-off balance sheet levereage. To address such financial crisis, the resilience of Islamic banking needs to be developed. Therefore, this paper searches the level of resilience of Islamic banking by building the Islamic Banking Resilience Index (IBRI). The level of resilience is analyzed through the construction of the composite index. The composite is compiled on the basis of several single variables index. Its construction follows an ideal sequence of five steps: theoretical framework, data selection, normalization, weighting and aggregation, and visualization of the result. Twelve variables are used to construct the composite index by using monthly data since January 2010 until December 2016. The composite index is able to figure out the resilience level of Islamic banking in Indonesia over periods of observation. At the resilience level, Islamic banking is able to deal with shocks and stresses, while keep providing financial services. The level of resilience is capable of preserving the elements of banking sector not failing from both crash and stagnation phase. Therefore, construction of IBRI is important as surveillance tools and underlying reason for further policy response and implementation. The composite index, represented by IBRI, is able to show the level of resilience of Islamic banking in Indonesia. The paper finally suggests that the resilience of Islamic banking requires a solid capital and liquidity management in order to provide a stronger ability in absorbing shocks and promoting financial services.